Who is a Religious Naturalist?. Issue 3 (3rd July 2017) - Goodenough, Ursula
ABSTRACT: This article introduces Religious Naturalism, an inclusive collection of belief systems focused on one central commitment: current understandings of the natural world remain undistorted by religious believing. Religious naturalists seek to develop coherent and satisfying meta-versions of their interpretive, spiritual, and moral responses to the natural world.